Universal size-dependent nonlinear charge transport in single crystals of the Mott insulator Ca2RuO4 - G. Avallone (Nature Portfolio, 2021)
Abstract The surprisingly low current density required for inducing the insulator to metal transition has made Ca2RuO4 an attractive candidate material for developing Mott-based electronics devices. The mechanism driving the resistive switching, however, remains a controversial topic in the field of strongly correlated electron systems. Here we probe an uncovered region of phase space by studying high-purity Ca2RuO4 single crystals, using the sample size as principal tuning parameter. Upon reducing the crystal size, we find a four orders of magnitude increase in the current density required for driving Ca2RuO4 out of the insulating state into a non-equilibrium phase which is the precursor to the fully metallic phase. By integrating a microscopic platinum thermometer and performing thermal simulations, we gain insight into the local temperature during simultaneous application of current and establish that the size dependence is not a result of Joule heating. The findings suggest an inhomogeneous current distribution in the nominally homogeneous crystal. Our study calls for a reexamination of the interplay between sample size, charge current, and temperature in driving Ca2RuO4 towards the Mott insulator to metal transition.